The Linguistic Rhetoric Of The Visual Image In The Arabic Digital Poetry According To The Receiving Theory. A Reading In The Digital Paintings Of Souad Oun - boulahaia, Linda; medjenah, djmel (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : With the development of communicative digital media, creators of various artistic genres and have found an important outlet for digital publishing, production, and reading, which necessarily means a change in the mechanisms and techniques of expression in terms of aesthetic dimensions and transcending the paper-based tradition into interactive and coherent creativity, imposing its linguistic, rhetorical and aesthetic specificities; thus generating new texts. An interactive or digital attribute has been added to it, such as an interactive novel or digital poem, as if the digital and interactive medium added a different aesthetic to the text. This included components that were topped by the eloquence and culture of the static and moving visual image,as visual signs full of connotations and effects accompanying the text: such as rhythm, generic, diction, and multiple audio levels. A new aesthetic was formed, with its levels, importance, and impact on reading the text or in the breadth of its relationship with cultural and technological contexts and patterns. In addition, we also seek to reveal the aesthetics of the digital flash poetry and its relationship to the recipient and to search and analyze digital effects such as image, sound, and external textual indicators. In reading the text and in reporting its levels, we aim toniest new media in the text and make it a part and tributary of the discourse in terms of different levels such as image, music, and output, which can be considered aesthetic digital awareness, which has its impact and presence in the digital text.